PENGARUH KUALITAS AKTIVA PRODUKTIF TERHADAP RETURN ON ASSET PADA BANK BRI SYARIAH (PERSERO) - Dendy Andriano; Yulita Zanaria; Ardiansyah Japlani (Jurnal Akuntansi AKTIVA, 2021)
This study aims to determine whether the Quality of Earning Assets Has an Effect on Return On Assets at BRI Syariah Banks (Persero). Data obtained from the results of bank financial reports, especially regarding KAP and ROA for 5 consecutive years. The data analysis of this research was carried out using statistical analysis. The results of this study indicate that KAP (Earning Asset Quality) has an influence on ROA (Return On Asset) at PT Bank BRI Syariah. This is in accordance with the theory which states that the ability of bank management to manage problematic productive assets on total productive assets the higher the higher the quality of the productive assets which will affect the bank's ability to generate profits.